After expulsion : 1492 and the making of Sephardic Jewry - Ray, Jonathan (Jonathan Stewart) (New York University Press, 2012)
On August 3, 1492, the same day that Columbus set sail from Spain, the long and glorious history of that nation's Jewish community officially came to a close. The expulsion of Europe's last major Jewish community ended more than a thousand years of unparalleled prosperity, cultural vitality and intellectual productivity. Yet, the crisis of 1492 also gave rise to a dynamic and resilient diaspora society spanning East and West. After Expulsion traces the various paths of migration and resettlement of Sephardic Jews and Conversos over the course of the tumultuous sixteenth century. Pivotally, t.